IMPLEMENTASI SISTEM KLAIM ASURANSI KENDARAAN BERMOTOR DI PT. IBS INSURANCE BROKING SERVICE, JAKARTA BERBASIS MOBILE - Christine Dewi; Kevin Hasudungan Brotosetyo Putro; Ramos Somya (CCIT Journal, 2016)
Claim's services in the PT. IBS Insurance Broking Service experiencing some obstacles in handling claim report. Claim officer cannot send notification letter and claim form to client who has not been having facsimile machine, error form filling, resulting the client must resend a new claim form, claim officer cannot quickly having assessment process permission. Therefore, a new system is needed to solve the claim activities problems. Claim system development aim to help claim officers to do their claim process. Analyzing claim process, system designing, implementing new system and testing new system, also analyzing test result, and writing research result are needed to develop new claim system. Claim applications created with Google Cloud Messaging Service, FPDF library, PHPExcel library, and REST Web Service. This research generates claim system helped with application based on mobile android platform. This research’s result shows the new system help client, claim officer, assessment officer, and claim head to do his/her job in the claim process